Limbic encephalitis due to GABAB and AMPA receptor antibodies: a case series. Issue 9 (9th October 2014) - Dogan Onugoren, M; Deuretzbacher, D; Haensch, C A; Hagedorn, H J; Halve, S; Isenmann, S; Kramme, C; Lohner, H; Melzer, N; Monotti, R; Presslauer, S; Schäbitz, W R; et al.
Abstract : Background: Two novel antibodies (abs) directed to γ-aminobutyric acid B receptor (GABAB R) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) in patients with limbic encephalitis (LE) were first described by the Philadelphia/Barcelona groups and confirmed by the Mayo group. We present a novel series for further clinical and paraclinical refinement. Methods: Serum and cerebrospinal fluid samples from a diagnostic laboratory were selected if found to be positive for GABAB R or AMPAR abs within a broad antineuronal ab panel. Data were retrospectively compiled. Results: In 10 patients, we detected abs to GABAB R. Median age was 70 years. Five of them were diagnosed with small cell lung cancer (SCLC). Intrathecal GABAB R ab synthesis was found in all six patients with sufficient data available (median ab-index: 76.8). On MRI, we found bilateral mediotemporal and in two cases cortical abnormalities. EEG revealed encephalopathy, partly with epileptiform discharges. Five patients received immunotherapy, two patients tumour treatment and three both therapies. Three patients died, in five patients cognitive functions declined, one patient improved slightly and one patient fully recovered. AMPAR abs were detected in three patients with mnestic disturbances. Median age was 60.7 years. The only female patient was diagnosed with ovarian cancer. None of the patients had intrathecal ab synthesis. MRI findings showed bilateral mediotemporal abnormalities. EEG was normal in all patients. Two of the three immunologically treated patients improved, one patient stabilised on a low level. Discussion: GABAB R and AMPAR abs are well associated with LE. GABAB R abs lead to severe clinical, neuroradiological and EEG abnormalities with poorer outcome.